Calophyllum inophyllum (CI) fruits kernel seed separator for biolubricant production line - Amiril Sahab, Abdul Sani; Muhammad Asyraaf Rusyaidi, Abdul Rauf; Aifa Arina, Mohd Alwi; Nur Hidayah, Mohd Nizam (2021)
Calophyllum lnophyllum (Cl) kernel seed is mostly known for its high oil content and is a type of vegetable oil that can be process to become biolubricant. Calophyllum Inophyllum (CI) kernel seed is mostly known for its high oil content and is a type of vegetable oil that can be process to become biolubricant. The oil is extracted from its kernel seed through the transesterification process. The oil is extracted from its kernel seed through the transesterification process. The main objective of this machine is to separate the seed from its shell before undergo transesterification process.